Electrical conductivity and transport properties of gold decorated amorphous carbon nanotubes/Epoxy Composites - Dian, L.Y.; Johan, M.R. (2015)
In this work, chemically synthesized, carboxyl groups functionalized, gold particles hybrid amorphous carbon nanotubes (a-CNT) were characterized. Transmission electron microscopy (TEM) shows that Au/a-CNT hybrid possesses smaller diameter of 10.2 nm than as-synthesized a-CNTs (40 nm). Moreover, even, well-ordered fringes formed on Au/a-CNT hybrid justified successful attachment of Au particles on a-CNT. Impedance plots shows lower resistivity on high Au content's Au/a-CNT hybrid. At the same time, Au/a-CNT hybrids possesses low electrical transference numbers as compared with as-synthesized a-CNTs. Au nanoparticles contribute conducting electrons to Au/a-CNT hybrids and tend to overcome the dominating ionic conduction of a-CNT as Au content exceeds 30 wt.